2019
DOI: 10.2174/1570159x17666190617095844
|View full text |Cite
|
Sign up to set email alerts
|

Partners in Crime: NGF and BDNF in Visceral Dysfunction

Abstract: : Neurotrophins (NTs), particularly Nerve Growth Factor (NGF) and Brain-Derived Neurotrophic Factor (BDNF), have attracted increasing attention in the context of visceral function for some years. Here, we examined the current literature and presented a thorough review of the subject. : After initial studies linking of NGF to cystitis, it is now well-established that this neurotrophin (NT) is a key modulator of bladder pathologies, including Bladder Pain Syndrome/Interstitial Cystitis (BPS/IC) and Chronic Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 222 publications
0
20
1
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF) and protein kinase Mζ (PKMζ), two of the molecules we examine in this study, critically contribute to LTP, memory and pain (Ji et al, 2003;Melemedjian et al, 2013;Price & Ghosh, 2013;Sacktor & Hell, 2017). Overexpression of BDNF has been linked to bladder inflammation, and the Val66Met mutation of BDNF can affect pain processing at the cortical level (Coelho, Oliveira, Antunes-Lopes, & Cruz, 2019). Recent studies have shown that BDNF contributes to visceral hypersensitivity in the colon (Fu et al, 2018;Zhang, Qin, Liu, Wang, & Yao, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) and protein kinase Mζ (PKMζ), two of the molecules we examine in this study, critically contribute to LTP, memory and pain (Ji et al, 2003;Melemedjian et al, 2013;Price & Ghosh, 2013;Sacktor & Hell, 2017). Overexpression of BDNF has been linked to bladder inflammation, and the Val66Met mutation of BDNF can affect pain processing at the cortical level (Coelho, Oliveira, Antunes-Lopes, & Cruz, 2019). Recent studies have shown that BDNF contributes to visceral hypersensitivity in the colon (Fu et al, 2018;Zhang, Qin, Liu, Wang, & Yao, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A research found that there were no nerve cells in endometriotic lesions originally, but BDNF and NGF can promote the generation of nerve tissue in endometriotic lesions ( 28) and the expression level of BDNF and NGF is correlated with pain degree of endometriosis patients (29). However, another study showed that the expression level of BDNF and NGF was no signi cant correlation with the degree of pain (30). The manifestations of endometriosis pain in different types and locations are varying and the mechanisms are different between peritoneal endometriosis and deep in ltrating endometriosis (DIE), the former may be correlated with the stimulation of cytokines and growth factor generated by lesions, while the latter is correlated with stimulation of various factors, as well as the deep lesions as reported in previous study (31) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NGF binds to the tropomyosin receptor kinase A (TrkA) receptor, which activates ERK 1/2 and Akt pathways and stimulates the transcription of pro-survival genes and inhibits cell apoptosis. BDNF binds to the TrkB receptor [ 19 , 20 ]. Both NGF and BDNF bind to the non-specific neurotrophin (NT) receptor p75 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study presented that children with traumatic brain injury showed statistically higher BDNF than NGF levels, both in the cerebrospinal fluid and plasma [ 16 ]. BDNF plays a pivotal role in the survival of neurons, regulation of neurite outgrowth and maintenance of synaptic connectivity of the central nervous system [ 19 ]. Studies on animal models show that exogenous administration of neurotropic factors reduces or even prevents neurological deficits and cell death after brain injury [ 17 ].…”
Section: Introductionmentioning
confidence: 99%